Demonstrasi Irigasi Drip Pada Budidaya Semangka Di Lahan Kering Desa Rempek Kabupaten Lombok Utara - Zainab, Siti; Wardhana, Agung Widya; Baharuddin, Baharuddin; Arifin, Zainal; Apzani, Wawan; Haryantini, Baiq Azizah; Hidayah, Mirfatul; Sunantra, I Made (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
The Community Service (PKM) implementation in Rempek Village aims to introduce drip irrigation technology suitable for highly porous land conditions and watermelon cultivation techniques on dry land. The implementation method includes preparation, execution, evaluation, and reporting stages. Land selection surveys and meetings with the community were conducted to ensure the suitability of the location and socialization of the objectives. The needs for tools and materials were carefully compiled, and an activity schedule was created to ensure timely execution of each phase. The results showed an increase in agricultural productivity and farmers' welfare due to drip irrigation technology and watermelon cultivation. In conclusion, this PKM successfully achieved its goals and positively impacted the Rempek Village community.